DUCTAL STENTING IN PULMONARY ATRESIA NEONATES WITH MULTIPLE CONGENITAL ANOMALIES AND SEPTIC CONDITION - Wibisono, Laurentia Utari; Gunawijaya, Eka; Pradnyana, Bagus Ari (Medicina; Vol 46 No 1 (2015): Januari 2015)
Neonates with  pulmonary  atresia  usually  appear  normal  at  birth with  pulmonary  circulationmaintained by the presence of a patent ductus arteriosus (PDA). Rapid deterioration will suddenlyocccur  if the duct close. Surgical shunt  is still be used as a standard protocol  in many centers as apalliative procedure. We report a 2 days-old, low birth weight, and mild cyanotic neonate with pulmonaryatresia and PDA accompanied by atresia ani, bladder and cloaca extropy, ambiguous genitalia andsepsis. We decided to perform PDA stenting because our patient have a high surgical shunt risk. Thisprocedure was very  important  to keep  the duct remains open until patient ready  for  total surgicalcorrection. [MEDICINA 2015;46:42-45]. Neonatus dengan atresia pulmonal biasanya tampak normal saat lahir dengan adanya patent ductusarteriosus (PDA) yang memelihara aliran darah paru. Kondisi neonatus akan segera memburuk jikaduktus menutup. Pembuatan shunt dengan pembedahan merupakan protokol standar yang masihdikerjakan di banyak pusat kesehatan. Kami melaporkan neonatus berusia 2 hari dengan berat badanlahir rendah dan sianosis ringan dengan diagnosis atresia pulmonal, PDA, atresia ani, ekstropi buli-buli dan kloaka, jenis kelamin ambigu, dan sepsis. Kami memutuskan untuk melakukan pemasanganstent pada PDA karena pasien kami memiliki risiko yang tinggi untuk pembedahan (pembuatan shunt).Tindakan ini sangat penting untuk menjaga duktus tetap terbuka sampai pasien siap untuk dilakukanoperasi koreksi. [MEDICINA 2015;46:42-45].
Keywords: ductal stenting, ductal dependent pulmonary blood flow, pulmonary atresia.